Материалы тшинецкого культурного круга с поселения Ходосовка-Диброва (из исследований 1988—1989 гг.) - Лысенко, С.Д. (Археологія і давня історія України, 2010)
Статья посвящена публикации материалов эпохи бронзы из исследований Среднеднепровской славянской экспедиции ИА АН УССР на многослойном поселении в ур. Диброва у с. Ходосовка Киево-Святошинского р-на Киевской обл. В 1988—1989 гг. Н.С. Абашиной здесь было раскопано 4 жилища и серия ям тшинецкого культурного круга. Приведена характеристика керамического комплекса, изделий из бронзы, камня и кремня. Выделены микроэтапы заселения исследованного участка в эпоху поздней бронзы. Стаття присвячена публікації матеріалів доби бронзи із досліджень Середньодніпровської слов’янської експедиції ІА АН УРСР на багатошаровому поселенні в ур. Діброва біля с. Ходосівка Києво-Святошинського району Київської області. У 1988—1989 рр. Н.С. Абашиною тут було розкопано 4 житла та серія ям тшинецького культурного кола. Приведено характеристику керамічного комплекса, виробів з бронзи, камня та кремня. Простежено мікроетапи заселення дослідженої ділянки за доби пізньої бронзи. The article is devoted to the publication of the Bronze Age materials from the research of the Middle Dnipro Slavic Expedition of the Institute of Archaeology of the Academy of Sciences of the USSR at the multilayer settlement in Dibrova tract near Khodosivka village of Kyiv- Svyatoshyn Region in Kyiv Oblast. In 1988 and 1989 N.S. Abashyna excavated here four dwellings and a series of pits of Tshynetska culture circle. Characteristics of ceramic series, of finds made of bronze, stone and flint are presented. The micro-stages of settling in the Late Bronze Age of the area researched are determined.